Comparative evaluation of the refrigeration compressor performance under different valve parameters in a trans-critical CO2 cycle. (May 2019) - Liu, Zhan; Cao, Xing; Wang, Tao; Jia, Wenguan; Duan, Zhenya
Highlights: A smaller valve lift size is preferred to enhance the valve life. An optimized spring stiffness improves trade-off between energy loss and leakage. Valve opening and closing are increasingly delayed as the plate mass increases. Abstract: This paper is to investigate the effects of valve parameters on the performance of a trans-critical refrigeration compressor numerically. A numerical model has been implemented in Matlab based on mass balance, first thermodynamic law, NIST REFPROP database for gas properties and thermodynamic relationships. Good agreement is indicated by comparing numerical results with our previous measured data. The impact of key parameters such as: valve lift, spring stiffness, valve plate mass and valve port area are particularly evaluated on variation of valve displacement, valve speed, in-cylinder pressure and in-cylinder mass. Results demonstrate that: with lift increasing valve plate will not remain open to the limiter for a while but bounce back to seat after hitting the limiter; the valve plate mass has significant influence on both the opening motion and the closing motion of valves.